ADMINISTRATORS' ASSESSMENT OF ICT SKILLS POSSESSED BY AACADEMIC STAFF OF COLLEGES OF EDUCATION IN SOUTH WESTERN NIGERIA (NAU Journal of Technology and Vocational Education, 2024)
The low ICT literacy level of NCE graduates in Nigeria was attributed to the levelof ICT skills possessed by lecturers in colleges of education. This study was aimed atinvestigating the ICT skills possessed by academic staff of colleges of education in southwestern Nigeria. Three research questions guided the conduct of the study. Survey designwas adopted for the study. The population of the study consisted of 379 programmeadministrators. 229 programme administrators constituted the sample used for the study.A questionnaire titled 'Teacher ICT Skills Assessment Questionnaire (TICTSAQ)' wasdeveloped by the researcher on a 4-point response scale and used for the collection ofdata. The instrument was validated by four experts. The reliability coefficient of theinstrument was 0.76 using the Cronbach Alpha. The analysis of data was done usingarithmetic mean. The results revealed that lecturers did not possess all ICT skills assessedin the study. It was recommended among others that teacher education curricula shouldbe reviewed by the government to include ICT skills not possessed by lecturers.